American Smart Cinema / Claire Perkins - Perkins, Claire
American Smart Cinema examines a contemporary type of US filmmaking that exists at the intersection of mainstream, art and independent cinema and often gives rise to absurd, darkly comic and nihilistic effects.Connecting the 'smart' sensibility to issues of expressive irony, generational divide and therapeutic culture, this bold new book describes a recent critical tradition in commercial-independent American filmmaking by exploring the unstable tone and dysfunctional themes of such films as The Royal Tenenbaums, Adaptation, The Squid and the Whale, Palindromes, The Last Days of Disco, Flirt, Ghost World, Your Friends and Neighbors, Donnie Darko and The Savages. Acknowledging the loaded forms of expression employed by these films, American Smart Cinema provides new directions for their study by discussing the self-conscious approach taken to film historical discourses of authorship, narrative and genre. Examining the smart film's taste for 'blank' style and issues of middle-class identity, the book provides a comprehensive account of smart cinema as an aesthetic category while also considering the cultural and political factors that have guaranteed it critical and popular success.